DEVELOPING VIRTUAL SMART FRACTION MEDIA BASED ON ADOBE FLASH FOR LEARNING FRACTION IN MATHEMATICS - Giyanto; Abdul Ghoni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study was initiated by the fact that Elementary School (SD/MI) teachers had not optimally utilized learning media, especially interactive media, in teaching fractions. Meanwhile, the rapid development of technology requires teachers to adapt and make use of technological advancements to support learning both inside and outside the classroom. The purpose of this study was to develop an effective, practical, interactive, and innovative learning media for mathematics learning, particularly on the topic of fractions. This study employed a research and development design. The results showed that Virtual Smart Fraction was highly feasible and effective as a learning medium. Its feasibility was supported by validation results from media experts with a score of 93.33% and from material experts with a score of 96.25%. Furthermore, its effectiveness was demonstrated through a small group test yielding 96.36% and a large group test yielding 95.14%. In addition, Virtual Smart Fraction improved the students’ average score from 62.58 to 89.82. Therefore, Virtual Smart Fraction was categorized as valid, highly feasible, and highly effective as a learning medium for mathematics learning.Keywords: ,